Dez anos do Programa de Subvenç\~ao ao Prêmio de Seguro Agrícola: Proposta de índice técnico para análise do gasto público e ampliaç\~ao do seguro - Gesmar Rosa dos Santos; Fabiano Chaves da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Production insurance is one of the main instruments of agricultural policy at the global level. It provides security against the damages caused by bad weather, as well as induces the adoption of technologies and preserves productive capacities. In several countries, the government have been helping agricultures to pay the premium by a grant. In Brazil, the "Programa de Subvenç\~ao ao Prêmio (PSR)" completed ten years in 2015, when it responded for only 1.51% of federal public spending with agriculture and livestock sector. This work takes as reference the agricultural insurance trajectory in Brazil, the United States, and in Spain crop insurance in order to analyze the PSR. We also create a technical index to support a possible expanding of Brazil's agricultural insurance system and it subsidy to the premium. We consider an historical interaction among the grant and the insured amount for each crop, apart from other factors. The proposal may change the concentration of the grant in the five main products from 86.8% to 67.8%, after three years by tripling the PSR size. Finally, we also present constraints, limits and suggestions to improve the instrument of public policy, and to encourage the growth of the agricultural insurance market in Brazil.
Keywords: Q12; Q14; Q18; 330; agricultural insurance; grant; agricultural policy; crops; index